Artificial or constructed wetlands a suitable technology for sustainable water management - Durán Domínguez de Bazúa, María del Carmen; Navarro-Frometa, Amado Enrique; Bayona, Josep Ma (Josep María) (CRC Press, Taylor & Francis Group, 2018)
Artificial or constructed wetlands are an emerging technology particularly for tropical areas with water scarcity. For big cities, the sustainable management of water resources taking into account proper use is always challenging. The book presents case studies illustrating the above. As plants and microorganisms are a fundamental part of the correct functioning of these systems, their contribution to the degradation of the organic matter and to the removal and transformation of the pollutant compounds present in the wastewaters is also a highlight of this book.